Use of a New Type of Mesh in Laparoplasties - Lanfranconi, Armando; Burjel, Jorge (Cirugía del Uruguay, 1981)
Presentation of a new type of absorbable synthetic mesh and description of its virtues deriver from the material employed in manufacture and its texture.